Swift heavy ion induced modifications in nano-crystalline microwave dielectric BaTi4O9 ceramics - (:unkn) unknown (ELSEVIER SCIENCE SA, 2010)
The pellets of BaTi4O9 were synthesized via a polymerized complex method and irradiated with 50 MeV Li3+ ions for two different fluences. The dielectric constant (epsilon(r)), and dielectric loss (tan delta) as a function of frequency (1 kHz-2 MHz) and temperature (40-200 degrees C) were measured for unirradiated and irradiated samples. The values of epsilon(r) for unirradiated and irradiated samples decreased with frequency at room temperature which is explained by Koops' model. The increase in dielectric constant after the irradiation shows that the damage occurs during irradiation and produces defects due to electronic processes and/or inelastic collisions. Micro-structural properties revealed that the size of pores/holes and their number increased with irradiation fluence giving rise to volume expansion porous defects. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ion irradiation; BaTi4O9; Citrate-gel processing; Dielectric properties; BARIUM-TITANATE; POLYMERIC PRECURSOR; IRRADIATION; TEMPERATURE; OXIDES